Pengaruh Entrepreneurial Orientation terhadap Kinerja UMKM dengan Innovation Capability sebagai Variabel Mediasi - Asnawi Hidayat; Jaelani Jaelani; Sunarmi Sunarmi; Cheesya Siska Adhiati; Adi Suryo Ramadhan (Fakultas Ekonomi & Bisnis, Univ, 2026)
This study aims to analyze the effect of entrepreneurial orientation on business performance, with innovation capability as a mediating variable, among Micro, Small, and Medium Enterprises (MSMEs) in Karanganyar Regency. The study employed a quantitative approach using a survey method administered to 200 MSME owners selected through purposive sampling. Data were collected via a questionnaire using a five-point Likert scale and analyzed using IBM SPSS Statistics through descriptive analysis, reliability testing, correlation analysis, linear regression, and the Sobel Test to examine the mediating effect. The results indicate that Entrepreneurial Orientation has a positive and significant effect on Innovation Capability, and that Innovation Capability has a positive and significant effect on Business Performance. Conversely, the direct effect of Entrepreneurial Orientation on Business Performance becomes insignificant after Innovation Capability is included in the model. The mediation test results show that Innovation Capability fully mediates the relationship between Entrepreneurial Orientation and Business Performance. These findings indicate that enhancing entrepreneurial orientation will be more effective in improving the performance of MSMEs if supported by adequate innovation capabilities. This study offers implications for the development of MSMEs through the strengthening of innovation capabilities as the primary mechanism for improving business performance.